Approaches to learn about employer learning - Mahmut Ablay; Fabian Lange (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2022)
The empirical literature on employer learning assumes that employers learn about unobserved ability differences across workers as they spend time in the labor market. This article describes testable implications that arise from this basic hypothesis and how they have been used to quantify the contribution of Job Market Signaling and human capital in measured returns to education. While the empirical basis is still thin, the results suggest that Signaling contributes at most about 25% to the observed returns to education.
Keywords: E24; J31; 330; Job Market Signaling; Human Capital; Returns to Education; Employer Learning